Monitoring of nucleophosmin oligomerization in live cells. (29th June 2018) - Holoubek, Aleš; Herman, Petr; Sýkora, Jan; Brodská, Barbora; Humpolíčková, Jana; Kráčmarová, Markéta; Gášková, Dana; Hof, Martin; Kuželová, Kateřina
Abstract: Oligomerization plays a crucial role in the function of nucleophosmin (NPM), an abundant nucleolar phosphoprotein. Two dual-color methods based on modern fluorescence confocal microscopy are applied for tracking NPM aggregates in live cells: cross-correlation Number and Brightness analysis (ccN&B) combined with pulsed interleaved excitation (PIE) and fluorescence-lifetime imaging microscopy (FLIM) utilizing resonance energy transfer (FRET). HEK-293T cells were transfected with mixture of plasmids designed for tagging with fluorescent proteins so that the cells express mixed population of NPM labeled either with eGFP or mRFP1. We observe joint oligomers formed from the fluorescently labeled NPM. Having validated the in vivo methods, we study an effect of substitutions in cysteine 21 (Cys21) of the NPM N-terminus on the oligomerization to demonstrate applicability of the methods. Inhibitory effect of mutations of the Cys21 to nonpolar Ala or to aromatic Phe on the oligomerization was reported in literature using in vitro semi-native electrophoresis. However, we do not detect any break-up of the joint NPM oligomers due to the Cys21 mutations in live cells. In vivo microscopy observations are supported by an in vitro method, the GFP-Trap immunoprecipitation assay. Our results therefore show importance of utilizing several methods for detection of biologically relevant protein aggregates. In vivo monitoring of the NPM oligomerization, a potential cancer therapy target, by the presented methods offers a new way to monitor effects of drugs that are tested as NPM oligomerization inhibitors directly in live cells.